(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This paper explores the theory of establishing and enforcing the National Integrity Standards in Jordan and the Kingdom of Saudi Arabia and compares the applied Jews in their legal, institutional, and policy framework. Based on official reports, international governance indices, and scholarly writings, the study proposes that five main pillars of integrity, transparency, accountability, rule of law, participation, and integrity culture are all efficient in influencing ethical governance. The results indicate that in both countries there are notable achievements that align with the international standards and of which this can be seen in the strategic plans of Jordan, through its National Integrity and Anti-Corruption Strategy (NIACS) 2020 2025 as well as that of Saudi Arabia in its governance reforms of its vision 2030. But the issues remain, such as irregular application of the rule of law in Jordan and the lack of mechanisms of taking part in the process of decision-making in Saudi Arabia. The researchers come to a conclusion that effective systems of integrity need not only the strong legal framework but also cultural change, institutional autonomy, the prolonged involvement of the people. It is recommended that the judicial capacity should be improved, participatory governance should increase, monitoring mechanisms, and the capacity to foster cross-border collaboration needed to reach more transparent, accountable, and trustworthy governance.